Unravelling consensus genomic regions conferring leaf rust resistance in wheat via meta‐QTL analysis. Issue 1 (17th December 2021) - Amo, Aduragbemi; Soriano, Jose Miguel
Abstract: Leaf rust, caused by the fungus Puccinia triticina Erikss (Pt), is a destructive disease affecting wheat ( Triticum aestivum L.) and a threat to food security. Developing resistant cultivars represents a useful method of disease control, and thus, understanding the genetic basis for leaf rust resistance is required. To this end, a comprehensive bibliographic search for leaf rust resistance quantitative trait loci (QTL) was performed, and 393 QTL were collected from 50 QTL mapping studies. Afterward, a consensus map with a total length of 4, 567 cM consisting of different types of markers (simple sequence repeat [SSR], diversity arrays technology [DArT], chip‐based single‐nucleotide polymorphism [SNP] markers, and SNP markers from genotyping‐by‐sequencing) was used for QTL projection, and meta‐QTL (MQTL) analysis was performed on 320 QTL. A total of 75 MQTL were discovered and refined to 15 high‐confidence MQTL (hcmQTL). The candidate genes discovered within the hcmQTL interval were then checked for differential expression using data from three transcriptome studies, resulting in 92 differentially expressed genes (DEGs). The expression of these genes in various leaf tissues during wheat development was explored. This study provides insight into leaf rust resistance in wheat and thereby provides an avenue for developing resistant cultivars by incorporating the most important hcmQTL. Core Ideas: Meta‐QTL (MQTL) analysis is an effective approach to synthesize QTL information. MQTL analysis reduced the confidence intervals for leaf rust resistance. MQTL allowed the identification of candidate genes.